DISTRIBUTION OF SHAFT RESISTANCE FOR SINGLE DRIVEN PILE - Harnedi Maizir; Nurly Gofar (Sekolah Tinggi Teknologi Pekanbaru, 2013)
This paper deals with the prediction of shaft resistance of single driven pile based on Meyerhoff formulation and empirical method based on SPT test. The accuracy of these predictions was evaluated by comparing the results with static load test (SLT ) and dynamic loading test analyzed by Pile Driving Analyzer (PDA ) and Case Pile Wave Analysis Program (CAPWAP )programs. The data for this study was collected from University Riau Hospital Project in Pekanbaru. The result of static and dynamic pile load test shows that only a small capacity of end resistance was mobilized due to insufficient pile deformation.